Claviform aspergillus‐related vegetation in the left ventricle of a patient with systemic lupus erythematosus. Issue 3 (1st June 2017) - Yamamoto, Tetsushi; Kasagi, Shimpei; Kurimoto, Chiyo; Imanishi, Takamitsu; Hayashi, Nobuhide; Morinobu, Akio; Saegusa, Jun
ABSTRACT: A 38‐year‐old woman was diagnosed with systemic lupus erythematosus and received immunosuppressive therapy. After 6 months of treatment, workup for low‐grade fever yielded elevated enzyme‐linked immunosorbent assay titers for Aspergillus antigen in serum and ascites, leading to the diagnosis of disseminated aspergillosis. Transthoracic echocardiography revealed a claviform vegetation attached to the left ventricular anterior septum. Two days after the start of antifungal Amphotericin‐B therapy, the patient suffered from several neurologic disorders. A second transthoracic echocardiography revealed that the vegetation decreased in size. Two weeks later, the vegetation increased again. Combination therapy of Amphotericin‐B and Voriconazole was initiated, and the vegetation eventually disappeared completely. © 2017 Wiley Periodicals, Inc. J Clin Ultrasound 46 :231–232, 2018